Splenectomy in Immune Thrombocytopenia: A Retrospective Analysis of 25-Year Follow-up Data from a Tertiary Health Clinic - ATAGÜNDÜZ, IŞIK; TOPTAŞ, TAYFUR (SPRINGER INDIA, 2022)
Immune thrombocytopenia (ITP) is a rare autoimmune disorder presenting with isolated thrombocytopenia. Splenectomy is still one of the treatment alternatives for these patients. Here we aim to analyze long term follow-up data of splenectomy in immune thrombocytopenia. This retrospectively designed study was conducted in a tertiary health clinic. Patients with ITP who were splenectomized between 1990 and 2015 were included. Response to treatment was interpreted as 'complete response', 'response' or 'no response'. The incidence of response loss was evaluated. Perioperative and long term complications and overall survival rates were determined. Out of 51 patients, who underwent splenectomy after 12 months of diagnosis, 47 achieved a response (92.2%). Of 47 patients who had a platelet count at least 30.000/mu L, 41 (87.2%) had CR. Incidence of loss of response was 10.5% (95% confidence interval (CI): 4%-26.1%) at 30 months. Two patients died, and overall survival rate was 97.4% (95% CI: 82.8%-99.6%) at 30 months of follow up. Considering the complications: two patients had venous thromboembolism, 11 had minor bleeding episodes and 15 suffered from perioperative infections. Our study suggests that splenectomy promises a high level of response with acceptable complication rates. Although less preferred recently, splenectomy should still be taken into consideration when remission is not achieved especially after 12 months of disease.
Keywords: Immune thrombocytopenia; Splenectomy; Corticosteroids; Hemorrhage; LAPAROSCOPIC SPLENECTOMY; LONG-TERM; VENOUS THROMBOEMBOLISM; ADULT PATIENTS; PURPURA; POPULATION; ELTROMBOPAG; ITP; MANAGEMENT; CHILDREN